Accounting for the Translation of Foreign Currencies: The Effects of Statement 52 on Equity Analysts (Book). - Ayres, Frances L. (The Accounting Review, 1988)
Reviews the book "Accounting for the Translation of Foreign Currencies: The Effects of Statement 52 on Equity Analysts," by Paul A. Griffin and Richard P. Castanias.